Design and analysis of frequecy selective surface - Audu, Babagana (2021)
The Frequency Selective Surface (FSS) is a two-dimensional periodic array of planar arrays made up of metal patches or aperture units. FSS has the ability to reflect or transmit all incident electromagnetic waves in certain frequency bands, demonstrating exceptionally great frequency selectivity. As a result, FSS displays the electromagnetic wave filter's function. FSS's patch elements array works as a band stop filter. Shielding the electronic equipment is one of the most common techniques to insulate RF electronics from radiated fields, and an EMI shield can be made out of wire mesh or metal foil. In this study, infinite array unit cell of a ring resonator band-stop has been designed and examined. FSS simulations are run on an Ardon 300D substrate with CST Microwave Studio for a variety of physical parameters, incidence angles, and polarizations. The S-parameter representation has been utilized to compare the simulation results. The Ring patch FSS has been designed based on an Arlon AD300D substrate with 7.17mm x 7.17mm unit cell dimensions. The study results indicated that Ring FSS band stop characteristics at center frequency of 14.958 GHz with bandwidth 34.1% works well on ku band(12 GHz to 18 GHz) unhindered. More so, the characteristics analysis of an EM wave as it propagates within the Ring FSS on both centre frequency and bandwidth by varying either of the ring radius or cell size. Finally, the study of ring FSS stability for transmission/reflection in TE and TM mode shows unvarying frequency response for various tested incidence angles (theta and phi). This study finding agreed with literature findings. This study finding indicating the viability of the study outcome can be implemented in EMI shield of satellite communication system and that will protect VSAT unit from interference.